Re-imaging the Modernity of Sierra Leone and Equatorial Guinea: Africa past and Africa present - Codling, Rosetta (2011)
This paper engages the concept of the imposed Modernity of Europe upon the African republics of Sierra Leone and Equatorial Guinea. Evidence of the encroachment of a ‘false’ Modernity upon Africa’s Sierra Leone and Equatorial Guinea are chronicled in the works of Donato Ndongo (Shadows of Your Black Memory) and Syl Cheney Coker (The Last Harmattan of Alusine Dunbar).